Antidepressive and antinociceptive effects of ethanolic extract and fruticuline A from Salvia lachnostachys Benth leaves on rodents - Santos, Joyce Alencar (PLoS One, 2017)
OBJECTIVES: This study investigated the antidepressant and antinociceptive effects of ethanolic extract (SLEE) and pure fruticuline A obtained from Salvia lachnostachys leaves on rats and mice. METHODS: In this study, SLEE (100 mg/kg, p.o. route) was evaluated for its effects on spared nerve injury (SNI) in rats. The animals were submitted to mechanical sensitivity, forced swim (FST) and cold sensitivity tests 10 and 15 days after surgery. SLEE (100 mg/kg, p.o.) and fruticuline A (3 mg/kg, p.o.) were also evaluated with respect to nociceptive behavior induced by formalin. In addition, clonidine-induced depressive-like behavior was also analyzed. RESULTS: The oral administration of SLEE for up to 15 days and the subcutaneous injection of 10 mg/kg of ketamine (positive control) significantly inhibited SNI-induced mechanical hyperalgesia and decreased immobility in the FST. On the 15th day of oral treatment, SLEE prevented the SNI-induced increase in cold sensitivity. In the formalin test, SLEE and fruticuline A significantly reduced the frequency of paw licking during the first and second phases and decreased the formation of edema. In locomotor analysis (open field test without clonidine treatment), SLEE and fruticuline A did not alter the response. SLEE and fruticuline A significantly attenuated clonidine-induced suppression of spontaneous locomotor activity (squares invaded and licking) and emotionality (grooming and freezing) compared with controls, similar to the naive group. CONCLUSION: SLEE exhibits antihyperalgesic, antidepressant, and antinociceptive effects, and fruticuline A appears to be at least partly responsible for the effects of SLEE. Together, these results demonstrate the antidepressive effects of SLEE and fruticuline A and indicate that both derivatives obtained from S. lachnostachys act against spontaneous neuropathic pain.